Disparities in dental service utilization among Alabama Medicaid children - Dasanayake AP, Li Y, Wadhawan S, Kirk K, Bronstein J, Childers NK. (Blackwell Synergy, 2002)
Objectives: Access to oral health care and utilization of available services are important factors in minimizing the oral health disparities among underserved minorities. Our objective was to evaluate the racial and other factors related to ‘realized access’ to oral health care among Alabama Medicaid children.